CONSUMPTION STUDY OF SUPPLEMENT ON MEMBER OF GYMS IN BANDUNG AND QUALITATIVE ANALYSIS OF STEROID IN SELECTED SUPPLEMENT - Damayanti, Sophi; Aria Fernandez, Eric; B Mahardhika, Andhika; Apriantono, Tommy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Sports supplements are popular commodity among bodybuilders. Unfortunately, a lot of bodybuilders use supplements with the addition of steroids. Therefore, the study of knowledge level and identification of steroid in supplements were needed. Hence, the aim of the present study was to measure knowledge of supplement in members of gyms and compare to the 4 year pharmacy students from the Bandung Institute of Technology. Furthermore, selected supplements from the previous study are then tested for steroids. The study was conducted in 2 gyms in Bandung (PK-A and PK-B) and Bandung Institute of Technology. Total 300 data of subjects were then statistically analyzed. Selected supplements were then tested for its content of steroid using Liebermann-Burchard method. The test was started with the determination of limit of detection. Further, qualitative analysis of steroid in 9 supplements was carried out. There was as much as 56% (PK-A) and 51% (PK-B) subjects who consumed bodybuilding supplement on a regular basis. A total of 49, out of 56 subjects, were in the range of 17-45 years of age (PK-A). While it was 48 out of 51 subjects in the range of 17-35 years of age at PK-B. Most of the subjects consuming supplement were either private employees (17 in PK-A; 10 in PK-B), entrepreneurs (20 in PK-A), or college students (12 in PK-A; 35 in PK-B). At PK-A, 40 out of 56 subjects has been a member since at least 3 years ago. While in PK-B, it was distributed rather evenly. Cumulatively, it was also observed most subjects consuming supplement were regularly exercising 4-5 times a week in PK-A (33) and PK-B (21). From the study, it was obtained that PK-A subjects (41.07%) have a higher percentage of subjects with above the average knowledge in comparison to the pharmacy students (34%). Based on the study, it was found that there is no significant difference at p>0.05 of the knowledge of members at PK-A and a lower percentage of average knowledge at PK-B in comparison to pharmacy students of the Bandung Institute of Technology. From 3 of the 9 samples showed positive results. Keywords: Knowledge, Liebermann-Burchard, Gyms, Steroid, Supplement. th